جرائم الانتفاع الواقعة على المال العام - د. نوفل علي الصفو (PROSPECTIVE RESEARCHES, 2023)
For the importance of finance in the state position in the global economic activates, the present research has been divided into two sections; introducing the public money and the crime of using the public money illegally. The aim is this research is to divide the crime of using the public money by the government employee because of using his official position and the crime of the damage which occurs an the eviction reprinted by the public interest. The research conceded some important points like stressing the penalty against such crimes.